The Impacts of Post-Colonial Condition towards the Main Character’s Trauma in Chris Cleave’s Little Bee - MURSALINA, ANNISSA (LANTERN (Journal on English Language, Culture and Literature), 2015)
Post colonialism is the result of colonialism. Generally, in post colonialism the values of colonialism still exist but only several people realize about this. This thesis discusses about the impacts of post colonialism that are experienced by the main character (Little Bee) in a novel “Little Bee” by Chris Cleave. The purposes of this thesis are to understand the symptoms of Post-Traumatic Stress Disorder (PTSD) toward the main character and to understand the aspects of post colonialism that are used by the main character to overcome PTSD. In the analysis of PTSD, it requires the knowledge of the reasons someone experiences PTSD. To write this thesis, the writer uses library method and psychological approach. The theories that are used in this analysis are post colonialism and PTSD. The result of this thesis shows that the main character, Little Bee uses several aspects of post colonialism, such as hybridity, mimicry, and stereotype. The usage of these aspects are triggered or are influenced by the situation.